The Effect of Organizational Commitment, Work Motivation and Individual Characteristics on Job Satisfaction: Pengaruh Komitmen Organisasi Motivasi Kerja dan Karakteristik Individual Terhadap Kepuasan Kerja - Lail, Kayyunrizalul; Oetardjo, Mas (Universitas Muhammadiyah Sidoarjo, 2021)
This study aims to determine the effect of organizational commitment, work motivation and individual characteristics on job satisfaction at CV. SUWARLANDONO. This research is a type of quantitative research with hypothesis testing. The sample used in this study were 92 employees at CV. Suwarlandono. The analytical tool used in this research is multiple linear regression analysis using SPSS version 25 for windows. . The primary data in this study were obtained from questionnaires whose measurements used a Likert scale which were tested for validity and reliability. The results of this study prove that the Effect of Organizational Commitment, Work Motivation, and Individual Characteristics Affects Job Satisfaction, besides the Effect of Organizational Commitment, Work Motivation and Characteristics Individually on Job Satisfaction has a simultaneous effect on job satisfaction